Simulation Game to Improve Knowledge and Attitude of Female Students Regarding Personal Hygiene During Menstruation - Andi Yulia Kasma; Marisna Eka Yulianita; Jufri Jufri;; Ayumar (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Personal hygiene during menstruation is crucial and should be carefully considered by every female student since poor personal hygiene can lead to disorders of the reproductive tract and organs. According to the 2020 Population Census results, Indonesia's population in 2020 was 270,203,917 (as of September 2020), with female adolescent aged 10 to 19 years by 22.73 million, or 48.49 percent of the overall youth population. This study aims to recognize the impact of simulation game approach to female adolescents’ knowledge and attitudes regarding personal hygiene during menstruation. This study is Quasi Experiment with Pretest-Posttest Nonequivalent Control Group Design. The participants were all female students in that number of samples was 64 respondents selected by purposive sampling. Snakes and ladders online games and true-false games are among the simulation games applied. The results of statistical tests obtained p = 0.000 (p<0.05) for knowledge variable and p = 0.000 (p<0.05) for attitude variable, indicated that there was a significant difference in the average score of respondents' knowledge and attitudes before and after they participate in a simulation game. It concluded that health education regarding personal hygiene during menstruation for female adolescent through simulation game (Persimu) may improve the knowledge and attitudes of female students at SMPN 12 Makassar so that they can behave in excellent menstrual hygiene. It is encouraged to school to provide frequent health education concerning personal hygiene during menstruation so that students can practice adequate menstrual hygiene.